Peran Branding Produk Dalam Pengembangan UMKM di Desa Kebondalem - Rafika Athiyah Kurniawan; Sonja Andarini (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Based on the various problems affecting MSMEs in Kebondalem Village, Bareng District, Jombang Regency. This requires assistance for MSMEs in marketing strategies and how to expand market share. The implementation method used in this service goes through several stages starting from surveying MSMEs, socializing the importance of branding, and providing assistance in making logo and banner designs. Based on the results of the service, it was found that Gotro Pangestu Mushroom MSME and Bunda Sila Cake Kitchen MSME received assistance in making logos and banners, while Restu Chips MSME and Pak Imam Tempe MSME only provided assistance in making banners.